Principles of Nuclear Medicine Self-Assessment and Board Review - Assadi, Majid (Springer International Publishing, 2018)
This book is the ideal study tool for all who are preparing for national or international nuclear medicine exams and in addition represents a truly outstanding quick review resource. More than 4200 questions, with comprehensive answers, are presented in order to enable readers to assess their knowledge and identify areas of weakness that require further self-study. Informative subchapters permit exploration of specific topics in greater depth, and practice tests will familiarize readers with the process of taking multiple-choice examinations. The book covers the entire spectrum of nuclear medicine, from basic science to clinical applications for diagnosis and treatment. Individual sections focus on oncology, bone and joint disorders, gastrointestinal disorders, acute care, cardiology, neurology and psychiatry, and renal disease. Principles of Nuclear Medicine is highly recommended for those who are taking nuclear medicine or radiology board examinations or recertifying their subspecialty certificate (CAQ) in nuclear medicine. More generally, it will be an asset for all trainees and practitioners of nuclear medicine and radiology.